KAJIAN ASPEK KEBIJAKAN DAN REGULASI DALAM MASALAH PENGELOLAAN LIMBAH CAIR INDUSTRI RUMAH TANGGA - Rahardjo, Petrus Nugro (Jurnal Air Indonesia, 2008)
Water pollution because of the domestic wastewater produced by the local community and their home industries in a big city, such as Jakarta, has already been inviting many environmental problems since the last ten years. Based on the research done by Directorat General Cipta Karya, Public Works Department RI, domestic wastewater in Jakarta delivers 75% of all pollutants in surface water pollution. Therefore many things should be done to solve those water pollution problems. A lot of environmentally related rules have established in Indonesia, but they are not able to be optimally implemented because of some weaknesses of the environmental rule contents. One of the solving options is to create a perfect regulation system for wastewater management. The laws for home industry wastewater management, especially in big cities, have to be perfectly completed, mainly in the field of standard, operation and procedure, the wastewater quality standard, the adequate and qualified technology, the landscape and building planning and the institutional coordination. If the all environmental regulations are well synchronized, the law enforcement will be simply implemented. By applying them consistently, the water pollution control will be handled well.Ã‚Â Keywrods : Environmental Regulation, Home Industry Waste Water, Institutional Coordination Ã‚Â